Transmission Performance Analysis of Universal Coupling Spider - Wenjun Mao; Yinhua Zhang; Weihua Song; Changhai Tian; Guoliang Geng; Haiquan Li (Jixie chuandong)
Taking the universal coupling with spider of heavy-duty maintenance machinery as study object， the kinematics theory is used to analyze the performance of the universal coupling with spider when the input shaft rotates at a uniform speed， and the output shaft rotates periodically unevenly around the circumference. It quantitatively expressed the unevenness of the universal coupling with spider from the aspects of angular speed ratio， coefficient of unevenness and angular acceleration. The results indicate that， with the increase of the angle and rotational speed of the input / output shaft of universal coupling with spider， the maximum angular acceleration of the output shaft increases， so its maximum inertia moment increases. The angle between the input / output shaft of the universal coupling with spider is a key parameter that affects its unevenness. When the angle between the input / output shaft of the universal coupling with spider increases， the fluctuation of the output shaft rotation angle increases， so reducing the input / output shaft angle is the only way to improve the transmission efficiency of the universal coupling with spider.